2020
DOI: 10.1071/rd20130
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus surface protein induces oxidative stress by increasing peroxides and inhibiting antioxidant defences in human spermatozoa

Abstract: Hepatitis B virus (HBV) infection may affect sperm motility in patients with HBV. HBV surface protein (HBs) decreases mitochondrial membrane potential, impairs motility and induces apoptotic-like changes in human spermatozoa. However, little is known about how human spermatozoa respond to reactive oxygen species (ROS; mainly peroxides) induced by HBs. In this study, HBs induced supraphysiological ROS levels in human spermatozoa and reduced the formation of 2-cell embryos (obtained from hamster oocytes and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…To our knowledge, no previous studies have evaluated the interaction effect of both spouses’ HBV infection prior to pregnancy on risk of CHDs in offspring. HBV infection has been reported to affect not only oocytes but also sperm, and there may be an interaction effect of spouses’ preconception HBV infection statuses . In this study, increased CHD risks were observed only in women previously infected with HBV with uninfected men or previously infected men with uninfected women prior to pregnancy.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…To our knowledge, no previous studies have evaluated the interaction effect of both spouses’ HBV infection prior to pregnancy on risk of CHDs in offspring. HBV infection has been reported to affect not only oocytes but also sperm, and there may be an interaction effect of spouses’ preconception HBV infection statuses . In this study, increased CHD risks were observed only in women previously infected with HBV with uninfected men or previously infected men with uninfected women prior to pregnancy.…”
Section: Discussionmentioning
confidence: 53%
“…HBV infection has been reported to affect not only oocytes but also sperm, and there may be an interaction effect of spouses' preconception HBV infection statuses. [27][28][29][30][31][32][33] In this study, increased CHD risks were observed only in women previously infected with HBV with uninfected men or previously infected men with uninfected women prior to pregnancy. Moreover, previously infected men with uninfected women had a higher prevalence of CHDs in offspring than previously infected women with uninfected men.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It destroys various body tissues and causes a variety of diseases, including diabetes, hepatitis, and neurodegenerative diseases. 85 Many viruses induce oxidative stress; such as respiratory syncytial virus (RSV), 86 EBV, 87 Pseudorabies virus (PRV), 88 Canine distemper virus (CDV), 89 Hepatitis B virus (HBV), 90 Mayaro virus (MAYV), 91 SARS-CoV-2, 92 Hepatitis C virus (HCV), 93 Human immunodeficiency virus(HIV), 94 Human papillomavirus (HPV), 95 Rotavirus, 96 Rabies virus, 97 Rubella virus (RV), 98 HSV, 99 ZIKV, 100 Japanese encephalitis virus (JEV), West Nile virus (WNV), Tick-borne encephalitis virus (TBEV), 101 Dengue virus (DENV), 102 Chikungunya virus, 103 Nipah virus (NiV), 104 Bovine leukemia virus (BLV), 105 Influenza a virus, 106 Chandipura virus (CHPV), 107 Newcastle disease virus (NDV), 108 African swine fever virus (ASFV), 109 Grass carp reovirus (GCRV), 110 and E. huxleyi virus (EHV). 111 Melissa has been proven to have anti-oxidative properties 50 and applies one of its antiviral properties through the same property.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…HBV surface proteins (HBs) exposure of sperm cell could cause sperm dysfunction and sperm death because of reactive oxygen species (ROS) generation and alteration of glutathione (GSH) peroxidase 4 (GPX4) activity. [17][18][19][20] GPX4 is currently regarded as the molecular marker and key regulator of ferroptosis. 21 Oxidative stress and GPX4 dysfunction are essential for ferroptosis.…”
Section: Introductionmentioning
confidence: 99%